Detection of prostate cancer DNA using tetrapods based disposable paper ecofriendly biosensor device. Issue 6 (8th October 2020) - Gautam, Aarti; Singhal, Chaitali; Mishra, Annu; John, Alishba T.; Gautam, Uttam K.; Abolhassani, Reza; Adelung, Rainer; Kumar Avasthi, Devesh; Kumar Mishra, Yogendra
Abstract: The present work reports an enhancement in early diagnosis of DNA of prostate cancer by a rapid and sensitive biosensor. The genosensor platform was designed and fabricated using cost‐effective and disposable paper‐based electrodes. Herein, the bio‐nano‐interface was developed by immobilization of probe DNA of prostate cancer on the zinc oxide tetrapods modified paper electrode. The genosensor was characterized by scanning electron microscopy, transmission electron microscopy, synchrotron X‐ray photoelectron spectroscopy, cyclic voltammetry and impedance spectroscopy. The nano‐engineered genosensor was tested and found to be selective to prostate cancer. The sensor could detect as low as 1 pM of prostate cancer DNA with the linear detection range from 50 µM to 1 pM. The paper‐based genosensor also proved to be advantageous in terms of easy preparation, low specimen volume, homogenous distribution of nanostructures onto the surface and cost‐effectiveness. The present work demonstrates the enormous potential of DNA biosensor as a rapid and specific diagnostic tool to be used for the detection of prostate cancer DNA.